LncRNA MIR503HG regulates NETs‐mediated NLRP3 inflammasome activation and NSCLC metastasis by enhancing the ubiquitination of C/EBPβ - Xin Ye; Chen Fang; Weiwei Hong; Xiaoying Qian; Biao Yu; Bingbiao Zhou; Xinyuan Yao; Dengying Chen; Chengsi Shu; Chuanhong Luo; Yong Wang; Yong Li (Clinical and Translational Medicine)
Abstract Background Neutrophil extracellular traps (NETs) are pivotal in the metastasis of non‐small cell lung cancer (NSCLC). Our previous research demonstrated that NETs facilitate NSCLC metastasis by triggering the stimulation of the NOD‐like receptor protein 3 (NLRP3) inflammasome, which is mediated through the suppression of the long non‐coding RNA MIR503HG. However, the precise molecular mechanisms linking MIR503HG to NLRP3 are still not fully understood. Methods By employing protein mass spectrometry and the Human TFDB database, key molecules involved in NLRP3 regulation were identified. The involvement of CCAAT enhancer binding protein beta (C/EBPβ) in NSCLC metastasis was examined in both cellular and animal models. Dual‐luciferase and CUT&RUN assays confirmed the mechanism by which C/EBPβ controls NLRP3. The regulatory relationship between MIR503HG and C/EBPβ was explored through RNA pulldown, RNA immunoprecipitation and coimmunoprecipitation assays. Additionally, methylation‐specific PCR and other studies revealed that NETs suppress MIR503HG via DNA methylation. Results We found that C/EBPβ mediates the regulation of NLRP3 by MIR503HG. Further investigation confirmed that C/EBPβ promotes the migration and invasion of NSCLC both in vivo and in vitro and is highly expressed in NSCLC tissue. Mechanistically, C/EBPβ binds to the NLRP3 promoter to promote NLRP3 expression. Conversely, MIR503HG suppressed C/EBPβ expression by facilitating C/EBPβ interaction with the E3 ubiquitin ligase RNF43, which in turn reduced NLRP3 expression and NSCLC metastasis. Meanwhile, we investigated the mechanism by which NETs inhibit MIR503HG expression and found that DNA methylation is involved in the suppression of MIR503HG by NETs. Additionally, reversing this methylation partially restored MIR503HG and NLRP3 expression and mitigated the metastatic effects of NETs in NSCLC. Conclusions This study emphasises the critical roles of C/EBPβ and DNA methylation in NETs‐mediated NSCLC metastasis. These findings unveil C/EBPβ and DNA methylation as potential novel targets for NSCLC with high NETs expression. Key points NETs suppress the expression of MIR503HG by inducing promoter DNA methylation. C/EBPβ binds to the NLRP3 promoter to promote NLRP3 expression. MIR503HG inhibits the expression of C/EBPβ protein by promoting the interaction between C/EBPβ and the E3 ubiquitin ligase RNF43, thereby repressing NLRP3 expression.